Outcomes of a multicomponent safe surgery intervention in Tanzania's Lake Zone: a prospective, longitudinal study. (31st May 2021) - Alidina, Shehnaz; Menon, Gopal; Staffa, Steven J; Alreja, Sakshie; Barash, David; Barringer, Erin; Cainer, Monica; Citron, Isabelle; DiMeo, Amanda; Ernest, Edwin; Fitzgerald, Laura; Ghandour, Hiba; et al.
Abstract: Background: Evidence-based strategies for improving surgical quality and patient outcomes in low-resource settings are a priority. Objective: To evaluate the impact of a multicomponent safe surgery intervention (Safe Surgery 2020) on (1) adherence to safety practices, teamwork and communication, and documentation in patient files, and (2) incidence of maternal sepsis, postoperative sepsis, and surgical site infection. Methods: We conducted a prospective, longitudinal study in 10 intervention and 10 control facilities in Tanzania's Lake Zone, across a 3-month pre-intervention period in 2018 and 3-month post-intervention period in 2019. SS2020 is a multicomponent intervention to support four surgical quality areas: (i) leadership and teamwork, (ii) evidence-based surgery, anesthesia and equipment sterilization practices, (iii) data completeness and (iv) infrastructure. Surgical team members received training and mentorship, and each facility received up to a $10 000 infrastructure grant. Inpatients undergoing major surgery and postpartum women were followed during their stay up to 30 days. We assessed adherence to 14 safety and teamwork and communication measures through direct observation in the operating room. We identified maternal sepsis (vaginal or cesarean delivery), postoperative sepsis and SSIs prospectively through daily surveillance and assessed medical record completeness retrospectively through chart review. We compared changes in surgical quality outcomes between intervention and control facilities using difference-in-differences analyses to determine areas of impact. Results: Safety practices improved significantly by an additional 20.5% (95% confidence interval (CI), 7.2–33.7%; P  = 0.003) and teamwork and communication conversations by 33.3% (95% CI, 5.7–60.8%; P  = 0.02) in intervention facilities compared to control facilities. Maternal sepsis rates reduced significantly by 1% (95% CI, 0.1–1.9%; P  = 0.02). Documentation completeness improved by 41.8% (95% CI, 27.4–56.1%; P  < 0.001) for sepsis and 22.3% (95% CI, 4.7–39.8%; P  = 0.01) for SSIs. Conclusion: Our findings demonstrate the benefit of the SS2020 approach. Improvement was observed in adherence to safety practices, teamwork and communication, and data quality, and there was a reduction in maternal sepsis rates. Our results support the emerging evidence that improving surgical quality in a low-resource setting requires a focus on the surgical system and culture. Investigation in diverse contexts is necessary to confirm and generalize our results and to understand how to adapt the intervention for different settings. Further work is also necessary to assess the long-term effect and sustainability of such interventions.